A concrete joint collaboration - Siti Nur Azwin, Zulkapri (2022)
A MASTER Service Agreement (MSA) was asigned between Universiti Malaysia Pahang (UMP) and Petronas Technical Training Sdn Bhd (PTTSB) that owns Institut Teknologi Petroleum Petronas (INSTEP) on June 19 at the state-of-the-art training centre in Batu Rakit, Terengganu.